Analisis pelaksanaan program indonesia sehat dengan pendekatan keluarga (PIS-PK) pada Puskesmas di Kabupaten Nagan Raya - Darmansyah Darmansyah (Jurnal SAGO Gizi dan Kesehatan, 2021)
Background: The achievement indicators of the healthy Indonesia program with a family approach (PIS-PK) at the Nagan Raya District Health Center was still low. The implementation of the PIS-PK program was only training, preparation, analysis of the initial healthy family index. In contrast, further intervention and analysis have not run optimally, so the existing data has not been used appropriately.Objective: The purpose of the study, to analyze the implementation of the healthy Indonesia program with a family approach at the Public Health Centers (PHC) in Nagan Raya Regency.Method: This research design is a cross sectional study conducted in Nagan Raya Regency in 2021. The data were collected using a questionnaire with a sample size of 70 officers. The measurement of the variables of government support, infrastructure, community support, human resources for health workers, monitoring and evaluation, was measured using a questionnaire sheet. Data analysis used Chi-Square statistical test and Binary Logistic Regression with a significance level of 95%.Results: The results was showed that there was a relationship between community support (p= 0.010, OR = 3.72), facilities and infrastructure (p= 0.019, OR= 3.2),, government support (p= 0.00, OR= 6.15), health personnel resources (p=0.008, OR= 4.8), monitoring evaluation (p= 0.007, OR= 4.52) with the implementation of the PIS-PK program. Based on the multivariate test, the dominant variable associated with the PIS-PK program was government support.Conclusion: The good government support is 6.15 times related to the success of the PIS-PK program implementation program compared to less government support.